Fabrication of Chitosan/Fe3O4 Nanocomposite as Adsorbent for Reduction Methylene Blue Contents - La Harimu; Sri Wahyuni; Nasrudin Nasrudin; Muhamad Jalil Baari; Dian Permana (Universitas Gadjah Mada, 2022)
Methylene blue (MB) is a dye in wastewater from textile industries that pollutes the water environment. Reduction of its content is necessary for protecting humans and the surrounding environment. This study fabricated chitosan/Fe3O4 nanocomposite through the mixture of chitosan from crab shell waste and magnetite (Fe3O4) from local sand iron with sodium tripolyphosphate (STPP)-sulfate crosslinker as an adsorbent to reduce methylene blue content. The obtained composite was characterized by Fourier Transform Infrared (FTIR) Spectrophotometer and X-Ray Diffraction (XRD) instrument. The contents of methylene blue before and after applying adsorbent-based nanocomposite were determined using an ultraviolet-visible (UV-Vis) spectrophotometer. FTIR characterization results show that chitosan and chitosan/Fe3O4 nanocomposite had successfully synthesized based on the typical vibrational peaks. The deacetylation degree of chitosan was 69.79%. Fe3O4, and chitosan/Fe3O4 nanocomposite, were confirmed by XRD patterns. The chitosan/Fe3O4 nanocomposite adsorption capacity reached 45.37 mg/g when adsorption occurred with 20 mg adsorbent, pH 9, and contact time of 1.5 h. Hence, the chitosan/Fe3O4 nanocomposite in this study has potency and is applicable to adsorb MB effectively.